2012
DOI: 10.5194/angeo-30-283-2012
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap arcs from the magnetosphere to the ionosphere: kinetic modelling and observations by Cluster and TIMED

Abstract: Abstract. On 1 April 2004 the GUVI imager onboard the TIMED spacecraft spots an isolated and elongated polar cap arc. About 20 min later, the Cluster satellites detect an isolated upflowing ion beam above the polar cap. Cluster observations show that the ions are accelerated upward by a quasistationary electric field. The field-aligned potential drop is estimated to about 700 V and the upflowing ions are accompanied by a tenuous population of isotropic protons with a temperature of about 500 eV.The magnetic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 100 publications
1
29
0
Order By: Relevance
“…The simultaneous acceleration of the precipitating electron beams demonstrates that the potential structure must extend to altitudes higher than the spacecraft, whereas the acceleration region is assumed to be confined at the topside of the ionosphere in the auroral zone (Maggiolo et al 2006;Teste et al 2007). A case study with a good conjunction between Cluster observations of precipitating electrons and ion outflows at high altitude, and optical observations of an arc by the TIMED spacecraft, confirmed the relationship between polar cap arcs and accelerated ion outflows with typical shape of inverted "V"s (Maggiolo et al 2012). A statistical study of ion outflows showed that they form elongated and sun-aligned structures with widths typically of the order of 30 km mapped to the ionospheric level.…”
Section: High Latitude Ionospheric Plasmamentioning
confidence: 92%
See 1 more Smart Citation
“…The simultaneous acceleration of the precipitating electron beams demonstrates that the potential structure must extend to altitudes higher than the spacecraft, whereas the acceleration region is assumed to be confined at the topside of the ionosphere in the auroral zone (Maggiolo et al 2006;Teste et al 2007). A case study with a good conjunction between Cluster observations of precipitating electrons and ion outflows at high altitude, and optical observations of an arc by the TIMED spacecraft, confirmed the relationship between polar cap arcs and accelerated ion outflows with typical shape of inverted "V"s (Maggiolo et al 2012). A statistical study of ion outflows showed that they form elongated and sun-aligned structures with widths typically of the order of 30 km mapped to the ionospheric level.…”
Section: High Latitude Ionospheric Plasmamentioning
confidence: 92%
“…A statistical study of ion outflows showed that they form elongated and sun-aligned structures with widths typically of the order of 30 km mapped to the ionospheric level. Their temperature is of the order of tens of eVs and they are accelerated to average energies of about 400-500 eV, with highest values up to 1-2 keV (Maggiolo et al 2011). Periods of northward or weak IMF are not favorable for low-latitude reconnection processes at the magnetopause.…”
Section: High Latitude Ionospheric Plasmamentioning
confidence: 99%
“…They are probably associated with polar cap arcs (Maggiolo et al 2012). It is an intermittent source of O + ions active only during prolonged periods of northward IMF and the total outflow flux associated with polar cap ion beams is low compared to other sources.…”
Section: Polar Cap Ion Beamsmentioning
confidence: 99%
“…Precipitating protons also exist in a polar arc [e.g., Peterson and Shelley , 1984], but their contribution to the polar arc's energy budget is significantly smaller than that of electrons [e.g., Hubert et al , 2004]. Polar arcs can be accompanied by upward ion beams at high altitudes (several Earth's radii above the ground), which originate from the quasi‐static field‐aligned acceleration driving ions and electrons upward and downward, respectively [e.g., Maggiolo et al , 2012, and references therein]. Plasma convection around the polar arcs exhibits a large variability with multiple reversals [e.g., Newell et al , 2009, and references therein].…”
Section: Introductionmentioning
confidence: 99%